Evaluasi Mutu Fisik dan Penentuan Nilai Sun Protecting Factor (SPF) Sediaan Lotion Ekstrak Etanol Daun Matoa (Pometia pinnata) - Bakri, Nur F.; Ola, Maria J.S; Pratiwi, Rani D. (Jurnal Biologi Papua, 2023)
Indonesia has high sun exposure, and most people work outdoors, so they need skin protection. One plant with the potential as a sunscreen is matoa leaf (Pometia pinnata). This study aimed to determine the physical quality and the Sun Protecting Factor (SPF) value of matoa leaf ethanol extract lotion, which were analyzed in vitro. Physical quality evaluation included organoleptic tests, homogeneity, pH, adhesion and spreadability, and SPF values obtained by the UV-Vis spectrophotometry method. Mansur Formula was used to calculate the SPF value. The results of the study showed FI (0.5%), FII (1%), and FIII (1.5%) obtained an average SPF value of 13.99 ± 1.45 (maximum protection), 22.27 ± 2.06 (ultra protection), 27.42 ± 0.54 (ultra protection). All formulas had good physical quality and had potential as sunscreens.  Key words: lotion; matoa leaves; SPF; sunscreen